Comparison of oral rifampicin with observation alone in treatment of acute central serous Chorioretinopathy - Anum Badar; Sadaf Khan; Sobia Usman Shah; Mohammad Tahir; Saman Babree (International Journal of Retina, 2020)
Introduction: A randomized control trial To compare efficacy of oral rifampicin in terms of drying of macula and decrease macular thickness with observation alone in patients of acute central serous Chorioretinopathy done in Layton Rahmatulla Benevolent Trust (LRBT) Free Eye and Cancer Hospital, Lahore from January 2017 to June 2017 Methods: After getting approval from hospital Ethical committee 140 patients of CSR were included in the study. The demographic details were noted and patients were randomized by lottery methods in two groups (group A& B). Group-A was observed for spontaneous resolution, routine treatment started if no improvement noted after 6 weeks of observation alone. Group B was given oral rifampicin 600mg per day for four weeks with liver function tests being done before commencement of treatment and after 2 weeks. Oral rifampicin was stopped if patient developed deranged liver function tests. Patients were followed up at 4 weeks for macular dryness and decrease macular thickness on optical coherence tomography(OCT). All the readings were carried out and noted by single person in order to minimize bias. Results: A total of 140 patents, 70 in each group, were included In study with mean age 38.77+7.74 in Group-A and 39.14+7.97 years in Group-B. regarding gender distribution 65.71 %(n=46) in Group-A and 613.43%(n=43) in Group-B were male. Comparison of outcome of treatment of acute central serous chorioretinopathy with oral rifampicin vs observation showed that 18.57 %(n=13) in Group-A and 41.43%(n=29) in Group-B had dry macula. Conclusion: We concluded that there is a significant difference in drying of macula in acute central serous chorioretinopathy with Rifampicin versus observation alone.